Preoperative and intraoperative factors predictive of complications and stricture recurrence following multiple urethroplasty techniques. Issue 4 (10th March 2021) - Kay, H. E.; Srikanth, P.; Srivastava, A. V.; Tijerina, A. N.; Patel, V. R.; Hauser, N.; Laviana, A. A.; Wolf, J. S.; Osterberg, E. C.
Abstract: Objectives: To investigate factors predictive of postoperative recurrence and complications in patients undergoing urethroplasty for stricture repair at a single center. Patients and methods: We retrospectively reviewed the records of 108 men who underwent urethroplasty for urethral stricture disease (USD) at a single center from 2016 to 2020. Demographic data, comorbidities, stricture history including etiology and prior treatments, patient‐reported symptoms, and outcomes data were collected for analysis. Data were analyzed in aggregate, then, stratified by type of urethroplasty performed. Descriptive statistics, univariate analysis, multivariate logistic regression, and intergroup comparisons were completed using STATA, with an alpha value of 0.05 and a confidence interval of 95%. Results: The median age of our patients was 58 years (interquartile range: 42‐69; range: 29‐83), with a median stricture length of 2.0 cm (interquartile range: 1.0‐4.5; range: 0.5‐10). The most common stricture etiology was iatrogenic (n = 33, 31%) and the most common urethroplasty was anterior anastomotic urethroplasty (n = 38, 35%), followed by buccal mucosal graft (BMG) urethroplasty (n = 35, 32%). Twenty‐four patients (22%) had stricture recurrence. Within the aggregate data, recurrence was significantly predicted by obesity (BMI > 30) (Odds Ratio [OR] 3.2, 95% Confidence Interval [CI]: 1.06‐10), and the presence of postoperative complications (OR 6.3, CI: 1.9‐21). The presence of any postoperative complications within 90 days was significantly predicted by stricture length ≥ 5 cm (OR 3.5, CI 1.09‐12) and recurrence (OR 6.0, CI 1.7‐21). Conclusion: Despite serving as the most definitive treatment for urethral stricture management, stricture recurrence and postoperative complications are not uncommon after urethroplasty. Obesity and stricture length negatively impact outcomes while a penile stricture location is associated with a lower recurrence rate, though this is not statistically significant.